Public Relations Strategies in Building an Inclusive Communication Climate in Starbucks Indonesia - Christine Priscilla; Rismi Juliadi; Friska Natalia (ULTIMA Comm, 2025)
Creating an inclusive work environment for individuals with disabilities is mandated by Law of The Republic of Indonesia Number 8 of 2016 and has become a strategic priority for companies. One major challenge is ensuring effective communication for the deaf community in the workplace. Starbucks Indonesia has taken progressive steps by opening its first sign language store in Tata Puri, Central Jakarta, as part of its public relations (PR) strategy to support inclusivity and diversity. This study aims to explore the PR strategies implemented by Starbucks Indonesia in building an inclusive communication climate. A qualitative descriptive approach and case study method were used. Data were collected through in-depth interviews with four participants from Starbucks Indonesia's management and staff, and observations at the sign language store. The theoretical framework includes strategic communication theory, PR strategies, and communication climate concepts to analyze how the company designs, implements, and evaluates PR strategies for inclusivity. The findings reveal that Starbucks Indonesia's PR strategy involves a combination of sign language training programs, public awareness campaigns, and technology-based customer service adjustments. There strategies not only enhance the company's image as a pioneer of inclusivity but also improve employee job satisfaction and customer loyalty within the deaf community. This research contributes to the development of inclusive communication strategies in business sector, offering practical implications for other companies seeking to implement similar initiatives. Additionally, it underscores the crucial role of public relations in promoting inclusivity and sustainability in Indonesia's food and beverage industry.